2020
DOI: 10.1177/2280800020917326
|View full text |Cite
|
Sign up to set email alerts
|

Color stability and degree of conversion of a novel dibenzoyl germanium derivative containing photo-polymerized resin luting cement

Abstract: Aim: To compare the color stability and degree of conversion (DC) of a resin cement containing a dibenzoyl germanium derivative photo-initiator (Variolink Esthetic) to resin cements containing conventional luting agents. Materials and Method: Spectrophotometry and Fourier transform infrared spectroscopy (FTIR) were used to compare the color stability and DC, respectively, of Variolink Esthetic compared to Calibra, Variolink-N, and NX3 resin cements. Ten specimens (1 × 2 mm2) of each resin cement were photo-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…27 The extent of conversion affects both physical and mechanical properties of composite. 28 In the author's opinion, low thickness of cement could be a reason due to the relining of post to the shape of canal. The surface of GFP is rough and the relined customized post is smooth.…”
Section: Discussionmentioning
confidence: 99%
“…27 The extent of conversion affects both physical and mechanical properties of composite. 28 In the author's opinion, low thickness of cement could be a reason due to the relining of post to the shape of canal. The surface of GFP is rough and the relined customized post is smooth.…”
Section: Discussionmentioning
confidence: 99%
“…Moszner et al in their studies claim that dibenzoyl germanium can be relatively easy synthetized and it has the highest extinction coefficient comparing to other photoinitiators used in the analysis. They also proved that Ivocerin has low cytotoxicity and no mutagenic effect [ 60 ].…”
Section: Novel Photoinitiatorsmentioning
confidence: 99%
“…The degree of conversion of cement containing Ivocerin is about 87%, but cement containing CQ and tertiary amine has about a 44% degree of conversion. Alkhudhairy et al also proved that Ivocerin-based cement has the highest Vickers micro-hardness and it is 47 VHN, additionally CQ-based cement has 33 VHN [ 60 ]. Delgado et al prove in their studies that cements containing Ivocerin has flexural strength very similar to CQ-cements.…”
Section: Novel Photoinitiatorsmentioning
confidence: 99%
“…11 FTIR based on light absorption was employed for DC assessment due to widespread application and reliability of outcomes. 25…”
Section: Discussionmentioning
confidence: 99%
“…11 FTIR based on light absorption was employed for DC assessment due to widespread application and reliability of outcomes. 25 It is reported that monomers containing Bis-GMA or tri-ethylene glycol dimethacrylate (TEGDMA) when substituted with urethane di-methacrylate (UDMA), flexural strength is increased. However, if Bis-GMA is replaced with TEGDMA, flexural strength is decreased.…”
Section: Discussionmentioning
confidence: 99%